2014
DOI: 10.1044/1059-0889(2013/13-0031)
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of Service Delivery for Children With Later-Identified Mild-to-Severe Hearing Loss

Abstract: Purpose This study examined diagnostic and intervention services for children identified with hearing loss (HL) after the newborn period. Method We compared ages at service delivery and length of delays between service delivery steps for 57 later-identified children with HL and 193 children who referred for assessment from the newborn hearing screen (NHS). For only later-identified children, regression models were used to investigate relationships among predictor variables and dependent variables related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
1
18
0
2
Order By: Relevance
“…For those children who had permanent HL when they started early intervention, it is likely that the intervention would have been more effective if the HL had been addressed. These results parallel the findings in Walker et al (2014) and again highlight the fact that hearing screenings are not a required component of Part C/birth-to-3 services in the federal Individuals with Disabilities Education Act. JCIH (2007) recommends that medical care providers refer patients for audiological testing in any cases of children who display speech and language delays regardless of whether they passed the NHS.…”
Section: Early Interventionsupporting
confidence: 80%
See 3 more Smart Citations
“…For those children who had permanent HL when they started early intervention, it is likely that the intervention would have been more effective if the HL had been addressed. These results parallel the findings in Walker et al (2014) and again highlight the fact that hearing screenings are not a required component of Part C/birth-to-3 services in the federal Individuals with Disabilities Education Act. JCIH (2007) recommends that medical care providers refer patients for audiological testing in any cases of children who display speech and language delays regardless of whether they passed the NHS.…”
Section: Early Interventionsupporting
confidence: 80%
“…This result leads us to believe that all families of children with mild HLregardless of socioeconomic status-may be at risk for delays in service delivery. It is unclear what other factors are contributing to timing of service delivery for children with mild HL, although the parent-reported reasons for delays between service delivery milestones for NHS-and later-identified groups of children with mild HL were similar to those reported from the larger OCHL cohorts in Holte et al (2012) and Walker et al (2014).…”
Section: Factors That Influence Timeliness Of Service Deliverymentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, as a whole, children with mild HL who were identified by the NHS were receiving follow-up services in as timely a fashion as children with more severe HL. On the other hand, Walker et al (2014) showed that children with mild HL who passed the NHS and were later-identified were at risk for delays in service delivery. The current study seeks to provide more information about service provision in a group of children with mild HL.…”
Section: Effects Of Cumulative Auditory Experiencementioning
confidence: 99%